1993
DOI: 10.1111/j.1365-2958.1993.tb00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory rhodopsin‐controlled release of the switch factor fumarate in Halobacterium salinarium

Abstract: Halobacterium salinarium responds to blue light by reversing its swimming direction. Fumarate has been proposed as one of the molecular components of this sensory system and is involved in the switching process of the flagellar motor. In order to obtain chemical proof for this role of fumarate, cells were stimulated with a pulse of blue light and lysed by rapid mixing with distilled water. The lysate contained fumarate in free and bound form, which were separated by ultrafiltration. The fumarate concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…For the archaeon Halobacterium salinarium, we have identified fumarate as a factor required for switching the direction of rotation of the flagellar motor (24) and found that its cytoplasmic concentration is controlled by the photoreceptors (23,26). In eubacteria, fumarate also has switch factor activity, as demonstrated in an in vitro system.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…For the archaeon Halobacterium salinarium, we have identified fumarate as a factor required for switching the direction of rotation of the flagellar motor (24) and found that its cytoplasmic concentration is controlled by the photoreceptors (23,26). In eubacteria, fumarate also has switch factor activity, as demonstrated in an in vitro system.…”
mentioning
confidence: 88%
“…The ether phase was quantitatively removed and evaporated under vacuum. The residual was redissolved in 0.2 ml of 0.1 M 3-amino-1-propanol buffer, pH 9.9, and assayed for fumarate as described by Montrone et al (26). The procedure was calibrated by adding fumarate as an internal standard to the boiling water used for lysing the cells.…”
Section: Methodsmentioning
confidence: 99%
“…The function of CheD and the CheC proteins, which build one of the three adaptation systems in B.subtilis [48], is unclear in Hbt.salinarum . The mechanism of action of the switch factor fumarate, which was discovered in Hbt.salinarum 20 years ago [49,50], is also unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…Besides CheY-P, fumarate is a further factor involved in flagellar motor switching, both in archaea ( H. salinarum , [46,47]) and bacteria ( E. coli and S. typhimurium , [48]). In E. coli , fumarate reductase (FRD) was identified as the target of fumarate at the motor, where it was shown to interact with the flagellar motor switch protein FliG [49].…”
Section: Introductionmentioning
confidence: 99%